Chemokines as mediators of angiogenesis - Mehrad, Borna; Keane, Michael P.; Strieter, Robert M. (Thrombosis and Haemostasis, 2007)
Chemokines were originally described as cytokines that mediate leukocyte recruitment to sites of inflammation. Members of a subgroup of chemokines, the CXC family, also play a critical role in both physiologic and pathologic angiogenesis, including in the context of chronic inflammation, fibrosis, and malignancy.A unique feature of this family of cytokines is that, on the basis of their structure and receptor binding, individual ligands display either angiogenic or angiostatic biological activity in the regulation of angiogenesis. In this review, we summarize the key literature in this growing field.
Keywords: Chemokine; chemokine receptor; angiogenesis; cancer